PENGARUH PENERAPAN METODE SOCRATIC CIRCLES DISERTAI MEDIA GAMBAR TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Afidah, Ihda Nuria; Santosa, Slamet; Indrowati, Meti (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT - This research aims to ascertain whether or not the application Socratic Circles method with images media affects the student?s creative thinking skill.This research is considered quasi-experiment research. The research was designed using Posttest-Only Control Group Design by applying Socratic Circles method with images media in experimental group and lectures methods, discussions, and presentations in control group. The population of this research were all strudents in X grade of SMA Negeri 2 Boyolali in academic year 2011/ 2012. The sample of this research was established by Cluster Random Sampling, in order to obtain class X-3 as experimental group and class X-2 as control group. The data was collected by using tests, documentation and observation form. The hypothesis was analized by using t-test. The conclusion of this research is that the application of Socratic Circles method with images media affects the student?s creative thinking skill. Key words: Socratic Circles method, Images Media, Creative Thinking Skill